Delineation of Prime and Marginal Lands in Karnataka for Sustainable Land Use - S.Srinivas and V. Ramamurthy, L.G.K. Naidu M. Lalitha, S. Dharumarajan (Journal of the Indian Society of Soil Science, 2016)
The present study delineated prime, moderate prime and marginal lands in Karnataka based on important soil and climatic parameters viz., soil depth, texture, presence of gravel, slope and length of growing period. The extent of total prime lands in Karnataka is 52.75 lakh ha (26.7% of TGA), in which Tumkur, Bijapur and Raichur districts have more prime lands i.e. 4.71, 3.79 and 3.55 lakh ha, respectively. The extent of marginal lands in Karnataka is 57.03 lakh ha (28.9% of TGA), and Belgaum district has large area (6.31 lakh ha) followed by Gulburga (3.86 lakh ha) and Bellary (3.43 lakh ha) districts. Irrigated areas with the problems of salinity/sodicity/wetness exists in 30.60 lakh ha predominantly in Tumkur (2.81 lakh ha), Gulburga (2.55 lakh ha), Raichur (2.25 lakh ha), Bijapur (2.14 lakh ha) and Bellary (1.94 lakh ha) districts. State government should frame strong land use legislations to restrict use of prime lands for non-agricultural purpose and pressure on marginal lands has to be reduced by evaluating the capability for present land use and accordingly suitable alternate land use can be suggested.